Visualising Obsessive-Compulsive Disorder: Exploring Colour, Repetition, And Composition In Painting As A Practice-Based Approach - Khirunnisa' Norli; Mohd Fazli Othman; Mohd Suhaimi Tohid (Badan Riset dan Inovasi Nasional (BRIN), 2025)
Obsessive-Compulsive Disorder (OCD) is a mental health condition characterised by intrusive, unwanted thoughts (obsessions) and the compulsion to perform repetitive actions to alleviate anxiety. This practice-based study investigates how OCD can be represented through paintings by utilising the visual elements of colour repetition and structured compositions. These artistic techniques are employed to reflect the cyclical, obsessive nature of the disorder, allowing for an exploration of its emotional and psychological impact. The research includes an analysis of existing artworks that address mental health, consultations with individuals living with OCD, and the creation of a series of paintings that embody the disorder's symptoms. Through colour repetition, the study symbolically portrays compulsive behaviour, while varied compositional structures represent the structured yet chaotic thoughts experienced by those with OCD. Additionally, the research examines how specific colours can evoke emotions such as anxiety, distress, and relief, which are prevalent in OCD. The study underscores the potential of fine art as a medium to express and communicate complex mental health experiences, aiming to raise awareness of OCD and offer a novel perspective on how painting can be used as a tool for mental health dialogue and understanding.